2015
DOI: 10.1175/mwr-d-15-0117.1
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Lake-Effect Convection during Landfall and Orographic Uplift as Observed by Profiling Radars

Abstract: A pronounced snowfall maximum occurs about 30 km downwind of Lake Ontario over the 600-m-high Tug Hill Plateau (hereafter Tug Hill), a region where lake-effect convection is affected by mesoscale forcing associated with landfall and orographic uplift. Profiling radar data from the Ontario Winter Lake-effect Systems field campaign are used to characterize the inland evolution of lake-effect convection that produces the Tug Hill snowfall maximum. Four K-band profiling Micro Rain Radars (MRRs) were aligned in a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
54
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(65 citation statements)
references
References 41 publications
10
54
1
Order By: Relevance
“…This distribution is noted particularly near Lake Ontario (Jiusto and Kaplan 1972;Wilson 1977;Minder et al 2015;Veals and Steenburgh 2015), as was the case for an LLAP event on 11 December 2013. The present study focuses on this particular event, observed intensively as part of the Ontario Winter Lake-effect Systems (OWLeS) project (Kristovich et al 2016).…”
Section: Introductionmentioning
confidence: 64%
See 3 more Smart Citations
“…This distribution is noted particularly near Lake Ontario (Jiusto and Kaplan 1972;Wilson 1977;Minder et al 2015;Veals and Steenburgh 2015), as was the case for an LLAP event on 11 December 2013. The present study focuses on this particular event, observed intensively as part of the Ontario Winter Lake-effect Systems (OWLeS) project (Kristovich et al 2016).…”
Section: Introductionmentioning
confidence: 64%
“…This study aims to present evidence corroborating (or refuting) each of these processes in one LLAP event observed during OWLeS. It builds on Minder et al (2015), who use K-band radar reflectivity profiles collected from four sites between the shore and the Tug to show that with increasing inland distance, echoes transition from a convective toward a stratiform morphology, becoming less intense and more uniform, in IOP2 and in other LeS events during OWLeS. The next section will describe the instruments and analysis methods used in the study.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…Typical capping inversion heights for most LES bands were found to be in the range of 1-2 km, whereas more intense LES bands had inversion heights of >3 km (Niziol 1987). Minder et al (2015) found that the inland enhancement of snowfall totals was not due to orographic invigoration of convection, which is a potential crucial finding with regards to determining what parameters may or may not modulate IE. Niziol et al (1995) classified different types of LES bands.…”
Section: Introductionmentioning
confidence: 75%